SPIRIT MITSAQAN GHALIDZA DALAM PERNIKAHAN SEBAGAI PENGUAT KELUARGA DI KALIMANTAN TENGAH - Musthofa, Khabib; Subiono, Subiono (USRATUNA: Jurnal Hukum Keluarga Islam, 2020)
This article tries to describe the opaque facts of divorce in Central Kalimantan. Because divorce is a life disaster, because the impact will be many ranging from children who become victims, family breakdowns, to the economy. This type of article is literature research with retrospective methods or looking at existing problems and then looking for solutions. Namely through the values of mitsaqan ghaliza, the results of this writing include the values of mitsaqan ghaliza teaching sincerity, full of commitment in building a family, because marriage is a sacred bond containing divine commitment not only with a partner but also involving Allah SWT. Then, one of the bright promises when there is a marriage is Muasyarah Bilma'ruf or hooking up well. These values will become the initial foundation for strengthening the family.